2021
DOI: 10.46281/aijssr.v6i1.978
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Feelings and Motivation of Afghan Students’ Regarding Studying at Chinese Universities

Abstract: Making a decision to study in foreign countries is considered one of the most difficult tasks. However, it is one of the most essential and valuable attempts for the students because in foreign countries the quality of lessons are high and they can make huge social relations with learners. Also, China accepts students from all over the world. This study examined the feelings, and motivations of Afghan students; the data was collected through google form and constructed interview which 99 students were the part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Although the preview link outside the classroom in the flipped classroom seemingly increases learning to "Preview videos can help us find key points and thinking directions, and reduce anxiety caused by lack of learning ideas." This result shows that pre-class activities in flipped classroom can help reduce cognitive load (Bahir & Huanghe, 2021). However, after experiencing the "flipped classroom" for the first time, students were unable to get rid of their dependence on the teacher and generated anxiety.…”
Section: The Contribution Of the Flipped Learning Environment To Valu...mentioning
confidence: 92%
“…Although the preview link outside the classroom in the flipped classroom seemingly increases learning to "Preview videos can help us find key points and thinking directions, and reduce anxiety caused by lack of learning ideas." This result shows that pre-class activities in flipped classroom can help reduce cognitive load (Bahir & Huanghe, 2021). However, after experiencing the "flipped classroom" for the first time, students were unable to get rid of their dependence on the teacher and generated anxiety.…”
Section: The Contribution Of the Flipped Learning Environment To Valu...mentioning
confidence: 92%
“…To foster an open, positive, and trustworthy learning environment for students, educators should prioritize creating ample opportunities for cooperation and exchange (Kiuppis, 2018). Establishing a harmonious and tacit relationship between teachers and students, as well as among students themselves, built on mutual trust and support, is essential (Bahir et al, 2021). It is crucial to cultivate a humanistic environment conducive to soft teaching practices (Ajmiri & Bahir, 2023).…”
Section: Cultivating Engagement Trust and Academic Enthusiasmmentioning
confidence: 99%
“…It is crucial to cultivate a humanistic environment conducive to soft teaching practices (Ajmiri & Bahir, 2023). In classroom teaching, teachers should offer more encouragement and fewer reprimands, along with intuitive demonstrations rather than empty preaching, fostering a lively and enjoyable atmosphere (Bahir et al, 2021).…”
Section: Cultivating Engagement Trust and Academic Enthusiasmmentioning
confidence: 99%
“…Studies have shown that consuming enough protein can increase the body's metabolism and cause the body to burn 150-200 more calories per day. Therefore, in order to improve the metabolic level, the three major nutrients in the diet should be appropriately matched (Bahir & Huanghe, 2021a).…”
Section: A Reasonable Combination Of Three Major Macronutrients Regul...mentioning
confidence: 99%